Designing Applications For Damage Reporting Of Public Facilities Using K-Means Clustering Algorithm - Rika Saljuni; Muhammad Sholahuddin; Fanema Putra Hartaret Harefa; Thines Raman; Juliansyah Putra Tanjung; N P Dharshinni (Institute of Computer Science (IOCS), 2022)
Public facilities are facilities provided for public purposes such as roads, street lighting, bus stops, sidewalks, and pedestrian bridges. The facilities provided are facilities that provide convenience for the community so that they must be maintained properly. Data mining is a process of dredging or collecting important information from large data. The data mining process often uses statistical, mathematical methods, to utilize artificial intelligence technology. The application designed uses 50 datasets which, after normalization, the number of data becomes 350 data, and after preprocessing the data used in the study is 81 data, with 4 attributes and 3 clusters. The results of the data processing resulted in the first data clustering based on the facility attributes produced as many as 29 data, the second data clustering based on the year attribute produced was 12 data, the third data clustering based on the attribute the resulting amount was 40 data